The Impact of Listening Condition on Background Noise Acceptance for Young Adults With Normal Hearing. - Gordon-Hickey, Susan; Moore, Robert E.; Estis, Julie M.; Bacon, Sid; Lansing, Charissa (Journal of Speech, Language & Hearing Research, 2012)
Purpose: To evaluate the effect of different speech conditions on background noise acceptance. A total of 23 stimulus pairings, differing in primary talker gender (female, male, conventional), number of background talkers (1, 4, 12), and gender composition of the background noise (female, male, mixed) were used to evaluate background noise acceptance. Method: A repeated measures research design was used. Participants were 15 female and 15 male young adults with normal hearing. Background noise acceptance was evaluated with the acceptable noise level (ANL). Results: The results revealed main effects of primary talker gender, number of background talkers, and listener gender. ANL was lower for conditions of a female primary talker and for conditions with multitalker backgrounds. Male listeners had significantly lower ANLs than female listeners. An interaction occurred between primary talker and background noise composition. For female primary talker conditions, the male talker backgrounds produced the lowest ANLs. For male primary talker conditions, the lowest ANLs were obtained with the female and male background talker conditions. Conclusions: Background noise acceptance depends on the listener and the stimulus condition. Stimulus selection can influence the measurement of ANL. The results support the use of the commercially available ANL materials.